Regression Forests for Efficient Anatomy Detection and Localization in Computed Tomography Scans - Criminisi, Antonio; Robertson, Duncan; Konukoglu, Ender; Shotton, Jamie; Pathak, S.; White, S.; Siddiqui, K. (Medical Image Analysis (MedIA), 2013)
This paper proposes a new algorithm for the efficient, automatic detection and localization of multiple anatomical structures within three-dimensional computed tomography (CT) scans. Applications include selective retrieval of patients images from PACS systems, semantic visual navigation and tracking radiation dose over time. The main contribution of this work is a new, continuous parametrization of the anatomy localization problem, which allows it to be addressed e ffectively by multi-class random regression forests. Regression forests are similar to the more popular classi fication forests, but trained to predict continuous, multi-variate outputs, where the training focuses on maximizing the con fidence of output predictions. A single pass of our probabilistic algorithm enables the direct mapping from voxels to organ location and size. Quantitative validation is performed on a database of 400 highly variable CT scans. We show that the proposed method is more accurate and robust than techniques based on ecient multi-atlas registration and template-based nearest-neighbour detection. Due to the simplicity of the regressor's contextrich visual features and the algorithm's parallelism, these results are achieved in typical run-times of only 4 seconds on a conventional single-core machine.